2018
DOI: 10.1530/ec-18-0324
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative carcinoid syndrome during small-bowel neuroendocrine tumour surgery

Abstract: Only few descriptions of intraoperative carcinoid syndrome (ioCS) have been reported. The primary objective of this study was to describe ioCS. A second aim was to identify risk factors of ioCS. We retrospectively analysed patients operated for small-bowel neuroendocrine tumour in our institution between 2007 and 2015, and receiving our preventive local regimen of octreotide continuous administration. ioCS was defined as highly probable in case of rapid (<5 min) arterial blood pressure changes ≥40%, not explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Authors were contacted and did not have full texts, so the two records were excluded. Eight studies which enrolled 864 patients (943 operations) met all inclusion criteria [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors were contacted and did not have full texts, so the two records were excluded. Eight studies which enrolled 864 patients (943 operations) met all inclusion criteria [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 5 studies, all patients had metastatic disease, with 4 studies selecting patients with liver metastasis (with or without other sites) [ 20 , 25 , 26 , 27 ], while the 5th study included patients with metastasis not exclusive of the liver (i.e., metastasis could be at other sites and not include the liver) [ 23 ]. All studies included patients with carcinoid syndrome, with 6 studies reporting the proportion of patients presenting with carcinoid syndrome, ranging between 46.7 and 85.2% [ 21 , 22 , 23 , 24 , 26 , 27 ]. One study excluded patients with carcinoid heart disease [ 26 ], and another did not specify whether carcinoid heart disease patients were included [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even if octreotide is the treatment of choice for carcinoid crisis according to its efficacy in carcinoid syndrome, data on its value for both managing and preventing the crisis are still scarce and conflicting [50][51][52][53][54][55][56]. All of the existing data are based on retrospective studies which used heterogenous definitions of carcinoid crisis, primary tumor origins, stages of disease, and octreotide regimens.…”
Section: Prevention and Management Of The Carcinoid Crisismentioning
confidence: 99%
“…In 2001, Kinney et al published the first and only study with a control group: they reported no complications during surgery in patients treated with octreotide (0/45, 0%) preoperatively, unlike those who did not receive any octreotide (7/67, 10%) [53]. The other publications, without any control group, described a low rate of carcinoid crisis (range from 0% to 3.4%) with the systematic use of octreotide regimen on the one hand, and a high rate of carcinoid crisis (range from 24% to 32%) despite the systematic use of octreotide regimen [50][51][52][54][55][56] on the other hand. Whatever the efficacy of octreotide regarding carcinoid crisis, it does not seem deleterious, as no increased rate of anastomotic leakage has been reported despite the octreotide-induced decrease of visceral perfusion.…”
Section: Prevention and Management Of The Carcinoid Crisismentioning
confidence: 99%
“…Besides surgical experience, anesthesia management might also be relevant. This is especially the case for patients undergoing surgery for hormonally active NEN because intra‐operative carcinoid syndrome develops in up to 55% of patients, regardless of preoperative prophylactic octreotide infusions 16 . Recently, Hallet et al 17 investigated the association between anaesthesiologist volume and postoperative morbidity after complex gastrointestinal surgery.…”
Section: Introductionmentioning
confidence: 99%